Troponin T Is Negatively Associated With 3 Tesla Magnetic Resonance Peripheral Nerve Perfusion in Type 2 Diabetes - Jende, Johann M. E.; Mooshage, Christoph; Kender, Zoltan; Schimpfle, Lukas; Juerchott, Alexander; Nawroth, Peter; Heiland, Sabine; Bendszus, Martin; Kopf, Stefan; Kurz, Felix T. (Frontiers in Endocrinology, 2022)
Objective The pathogenesis of diabetic polyneuropathy (DN) is poorly understood, and, given the increasing prevalence of DN, there is a need of clinical or imaging biomarkers that quantify structural and functional nerve damage. While clinical studies have found evidence of an association between elevated levels of troponin T (hsTNT) and N-terminal pro brain natriuretic peptide (proBNP) with microvascular compromise in type 2 diabetes (T2D), their implication in mirroring DN nerve perfusion changes remains unclear. The objective of this study was therefore to investigate whether hsTNT and proBNP assays are associated with MRI nerve perfusion in T2D. Methods In this prospective cross-sectional single-center case-control study, 56 participants (44 with T2D, 12 healthy control subjects) consented to undergo magnetic resonance neurography (MRN) including dynamic contrast-enhanced (DCE) perfusion imaging of the right leg. Using the extended Tofts model, primary outcome parameters were the sciatic nerve’s microvascular permeability (Ktrans), extravascular extracellular volume fraction (ve), and plasma volume fraction (vp) were quantified, as well as hsTNT and proBNP values from serological workup. Secondary outcomes were further clinical, serological, and electrophysiological findings. Results In T2D patients, hsTNT was negatively correlated with Ktrans (r=-0.38; p=0.012) and ve (r=-0.30; p=0.048), but not with vp (r=-0.16; p=0.294). HsTNT, Ktrans, and ve were correlated with peroneal nerve conduction velocities (NCVs; r=-0.44; p=0.006, r=0.42; p=0.008, r=0.39; p=0.014), and tibial NCVs (r=-0.38;p=0.022, r=0.33; p=0.048, r=0.37; p=0.025). No such correlations were found for proBNP. Conclusions This study is the first to find that hsTNT is correlated with a decrease of microvascular permeability and a reduced extravascular extracellular volume fraction of nerves in patients with T2D. The results indicate that hsTNT may serve as a potential marker for the assessment of nerve perfusion in future studies on DN.